Risk Factors Predicting Positive Margins at Primary Wide Local Excision of Cutaneous Melanoma. Issue 5 (May 2016) - Mangold, Aaron R.; Skinner, Ryan; Dueck, Amylou C.; Sekulic, Aleksandar; Pockaj, Barbara A.
Abstract : BACKGROUND: A small percentage of patients will have positive histological margins after primary wide local excision (WLE) of cutaneous melanoma (CM). Risk factors that predict marginal involvement at WLE remain unclear. OBJECTIVE: To identify risk factors associated with positive margins after WLE of CM. MATERIALS AND METHODS: A retrospective review of patients treated at a single institution for CM with sentinel lymph node biopsy from 1997 to 2011 was conducted. RESULTS: Positive margins occurred in 6% of patients. Patients with positive margins were older (72.4 vs 60.7, p < .001), had thicker tumors (3.6 vs 1.9 mm, p < .001), and often involved the head and neck region ( p < .001). Patients with positive margins at WLE had positive margins on initial biopsy ( p = .012) and a higher rate of a melanoma in situ component on initial biopsy (24% vs 11%, p = .02). The 5-year local recurrence rate was significantly different between those with positive and negative margins at WLE (16.0% vs 6.9%; p = .047). CONCLUSION: Positive margins after WLE are uncommon. When a patient has multiple risk factors for positive margins at WLE, histologically clear margins should be obtained through mapped serial excision or Mohs micrographic surgery.